Implementation of Circular Economy Concepts Through Eco-Enzyme Production in the Management of Food Left Waste in Mambal Village - PURNAMAWATI, Ida Ayu Putu Santi; LAKSMI, Putu Ayu Sita; SURIANI, Ni Nyoman (Indonesia Strategic Sustainability, 2024)
The waste problem is a severe issue in Indonesia, including on the island of Bali, which is famous for its natural beauty. MambalVillage in Badung Regency is the focus of the Real Work Lecture-Community Empowerment by Students (KKN-PMM) program from Warmadewa University. In this program, students attempt to overcome the problem of food waste by introducing the concept of a circulareconomy through the production of eco-enzymes. Eco-enzymes can be made from organic waste, especially food waste. Its use follows circular economy principles by converting waste into value-added resources. Through a series of activities, including collecting raw materials, holding demonstrations on making eco-enzymes, the KKN-PMM program succeeded in providing a practical solution to the food waste problem in Mambal Village. Active community participation, Apart from that, this program also integrates various fields of science, such as law, health, engineering, administration and economics, to improve prosperity and sustainability at the local level. Thus, the KKN-PMM program in Mambal Village is a concrete example of applyingthe circular economy concept to overcoming environmental problems. Through collaboration between students and the local community, this program provides practical benefits and creates harmonious and mutually beneficial relationships. The hope is that thiseffort can inspire other regions to face similar challenges in waste management, which is in line with circular economy principles that minimize waste and maximize resource utilization.